The prevalence of gingival recessions and its association with the width of attached gingiva, oral hygiene status, gingival conditions and tooth brushing - Rafi' A Al-Talib (University of Mosul, College of Dentistry, 2004)
This study highlights on examining 100 dental students within the clinical years program. The oral hygiene status and gingival conditions were diagnosed by using the plaque index score (Silness and Löe, 1964) and the gingival index score (Löe and Silness, 1963). On this basis, the width of the attached gingiva and the depth of the gingival pockets were evaluated. The gingival recessions were recorded and their heights measured from the cemento- enamel junction to the gingival margin. Questionnaires about method, time and frequency of tooth brushing and type of tooth brush used were recorded. The results showed that 33 students have one or more gingival recession, 18 students had one and 15 students had two or more; among them 5 had 3 and 2 had 4 recessions, and no significant correlation was found between oral hygiene and gingival recession, oral hygiene and width of attached gingiva, gingival conditions and gingival recession, gingival conditions and width of attached gingiva, width of attached gingiva and number of gingival recessions. No statistically significant differences were observed in oral hygiene status and gingival conditions among three groups of students (without, with one and with two or more recessions, respectively). No correlations were shown between different methods of tooth brushing, time of brushing and type of toothbrush used and gingival recessions. Only correlation was found between frequency of brushing and gingival recessions.